Associations of Preoperative Patient Mental Health and Sociodemographic and Clinical Characteristics With Baseline Pain, Function, and Satisfaction in Patients Undergoing Rotator Cuff Repairs. Issue 2 (February 2020) - Sahoo, Sambit; Ricchetti, Eric T.; Zajichek, Alexander; Evans, Peter J.; Farrow, Lutul D.; McCoy, Brett W.; Jones, Morgan H.; Miniaci, Anthony A.; Sabesan, Vani J.; Schickendantz, Mark S.; Seitz, William H.; et al.
Background: Shoulder pain and dysfunction are common indications for rotator cuff repair surgery, yet the factors that are associated with these symptoms are not fully understood. Purpose/Hypothesis: This study aimed to investigate the associations of patient and disease-specific factors with baseline patient-reported outcome measures (PROMs) in patients undergoing rotator cuff repair. We hypothesized that tear size and mental health status, as assessed by the Veterans RAND 12-Item Health Survey mental component score (VR-12 MCS), would be associated with baseline total Penn Shoulder Score (PSS) and its pain, function, and satisfaction subscale scores. Study Design: Cross-sectional study; Level of evidence, 3. Methods: We prospectively identified 12 patient factors and 12 disease-specific factors as possible statistical predictors for baseline PROMs in patients undergoing surgical repair of superior-posterior rotator cuff tears at a single institution over a 3-year period. Multivariable statistical modeling and Akaike information criterion comparisons were used to investigate the unique associations with, and relative importance of, these factors in accounting for variation in baseline PSS and its subscale scores. Results: A total of 1442 patients who had undergone surgery by 23 surgeons met inclusion criteria, with a baseline median total PSS of 38.5 (pain, 12; function, 24.2; satisfaction, 2). Adjusted R 2 in multivariable models demonstrated that the 24 general patient and disease-specific factors accounted for 22% to 24% of the variability in total PSS and its pain and function subscale scores. Large/massive tear size was significantly associated with worse PSS total score and function score but not pain or satisfaction scores. Lower VR-12 MCS was significantly associated with worse total PSS and all 3 subscale scores. Among other factors significantly associated with baseline PROMs were sex, race, preoperative opioid use, years of education, employment status, acromion status, and adhesive capsulitis. Lower VR-12 MCS, preoperative opioid use, female sex, and black race were the factors most strongly associated with baseline PROMs. Conclusion: Large/massive tear size, lower VR-12 MCS, and several additional patient and disease-specific factors are associated with baseline PROMs in patients undergoing rotator cuff repair. Further studies are needed to investigate whether these factors will also predict poor postoperative PROMs.